2016
DOI: 10.5294/edu.2016.19.1.5
|View full text |Cite
|
Sign up to set email alerts
|

La formación ciudadana en la educación obligatoria en Colombia: entre la tradición y la transformación

Abstract: Para citar este artículo / To reference this article / Para citar este artigo González-Valencia, G. A. y Santisteban-Fernández, A. (2016). La formación ciudadana en la educación obligatoria en Colombia: entre la tradición y la transformación. Educ. Educ., 19(1), 89-102. DOI: 10.5294/edu.2016.19.1.5 La formación ciudadana en la educación obligatoria en Colombia: entre la tradición y la transformación ResumenISSN 0123-1294 | Educ.Educ. Vol. 19. No. 1 | Enero-Abril de 2016 | pp. 89-102. 91La formación ciudad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 7 publications
0
8
0
14
Order By: Relevance
“…González-Valencia and Santisteban-Fernández (2016) found that although pre-service teachers in Colombia wanted to teach citizenship education, they were not sure how as it was not part of their programme. Cuenca et al (2016) also study pre-service teachers, but in Peru, and find discrepancies between curriculum expectations and pre-service teacher attitudes: for example, ‘approximately 40% of the teachers think that the poor are poor because they do not try hard enough and .…”
Section: Resultsmentioning
confidence: 99%
“…González-Valencia and Santisteban-Fernández (2016) found that although pre-service teachers in Colombia wanted to teach citizenship education, they were not sure how as it was not part of their programme. Cuenca et al (2016) also study pre-service teachers, but in Peru, and find discrepancies between curriculum expectations and pre-service teacher attitudes: for example, ‘approximately 40% of the teachers think that the poor are poor because they do not try hard enough and .…”
Section: Resultsmentioning
confidence: 99%
“…El diseño del cuestionario -de manera puntual la pregunta por las finalidades de la enseñanza de la historia-tomó como referencia la propuesta de Jürgen Habermas (1966) sobre los intereses que orientan la generación de conocimiento: técnico, práctico y emancipatorio. Esta propuesta se ha empleado en otros trabajos en la DCS, la historia y la geografía (Benejam-Argimbau, 2002;Catling, 2004;Evans, 1991;González-Valencia & Santisteban-Fernández, 2016).…”
Section: El Diseño De La Investigaciónunclassified
“…El crecimiento de los Estados nación, el debilitamiento de las fronteras, sumado al aumento de la inmigración, hacen surgir preguntas complejas sobre las nociones de diversidad y ciudadanía en un mundo global (Giddens, 1993).…”
Section: Diversidad Y Ciudadaníaunclassified
“…Estas transformaciones han impactado de manera incuestionable al sistema educativo y, sin excepción, a todas las comunidades educativas que se están enfrentando a una nueva realidad diversa y multicultural. El contexto que enmarca un sistema social es complejo, cambiante y de incertidumbre (Bajoit, 2003;Bauman, 2004;Beck, 1992;Giddens, 1993), no solo para quienes enseñan, sino para quienes han de definir los contenidos y estrategias para abordar la diversidad (Pérez, 2000;Ferrâo, 2010).…”
Section: Discusión Y Conclusionesunclassified